2019
DOI: 10.3389/fpsyg.2019.02262
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Juvenile Onset of Depression and Emotion Regulation Difficulties

Abstract: Juvenile onset of Major Depressive Disorder (MDD) is associated with increased likelihood of recurrent episodes of depression and more detrimental clinical trajectories. The aim of the current study was to investigate the effect of juvenile onset of MDD on emotion regulation as measured by self-report and Heart Rate Variability (HRV). Furthermore, we wanted to assess whether juvenile onset impacted the association between rumination and depressive symptoms. Sixty-four individuals with at least three prior epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 91 publications
2
8
0
1
Order By: Relevance
“…The present study examined the link between teachers' subjective happiness and positive (i.e., job satisfaction) and negative (i.e., turnover intention) job attitudes, as well as the interactive role of EI in this association in a sample of Spanish teaching professionals. As expected, our results showed that both subjective happiness and EI were significantly associated with higher job satisfaction, as well as with lower turnover intention among teachers (Miao et al, 2017 ; De Stasio et al, 2019 ). Additionally, moderation analyses showed the main effects of happiness and EI in explaining teachers' job attitudes; in particular, happiness and EI predicted both higher job satisfaction and lower turnover intention.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The present study examined the link between teachers' subjective happiness and positive (i.e., job satisfaction) and negative (i.e., turnover intention) job attitudes, as well as the interactive role of EI in this association in a sample of Spanish teaching professionals. As expected, our results showed that both subjective happiness and EI were significantly associated with higher job satisfaction, as well as with lower turnover intention among teachers (Miao et al, 2017 ; De Stasio et al, 2019 ). Additionally, moderation analyses showed the main effects of happiness and EI in explaining teachers' job attitudes; in particular, happiness and EI predicted both higher job satisfaction and lower turnover intention.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, our findings suggest that teachers experiencing high levels of happiness as well as perceiving themselves as emotionally intelligent may feel more capable of overcoming future teacher-related challenges and demands and that this may result in more positive attitudes toward their jobs and wider careers. The results from this study may add to the incipient literature on subjective well-being and dispositional factors as contributors to work-related well-being, as they show that happiness and EI may constitute beneficial and complementary resources that can influence teachers' perceptions of their work (De Stasio et al, 2019 ). Thus, these preliminary findings may contribute to developing comprehensive models integrating the JD-R theory and the broaden-and-build theory of positive emotions to achieve a better understanding of teachers' well-being (Granziera et al, 2021 ).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations